A experiência turística em narrativas de viagem : uma tentativa antropológica no ciberspaço - Camargo, Henrique Patto Pinho Vieira de (My University, 2015)
Consequence of the constant movement of a tourismologist trying to acclimatize to the anthropological gaze, and its ethnographic nuances, this paper seeks to complexify the understanding and uses of Touristic(s) Experience(s), either by scientific academy, as by the tourism trade. While searching theoretical basis for understanding the proposal by the Anthropology of Experience, by Victor Turner and Edward Bruner, and its scientific approach to Experience, highlighting its procedural form and ritual, personal and subjective, this work attempts to understand why a life story can only be perceived and felt by the person who experiences the realities that faces in different spaces that circulates throughout his life, and expresses the way that wants and is able to represent. Immersed in cyberspace, while experiencing methodologies for emergence of clues in this opened universe, plural and not fixed, allowing expressions decentralized and deterritorialized, according to the interests and meaningful guidelines of each person that externalizes them, search narratives in Travel blogs that can express representations about their traveling experiences, wrapped (in front) to a phenomenon that displaces individuals from their everyday space and time, such as tourism, which at the same time, enables moments of strangeness, of dramatic confrontation between their previous knowledge and the reality in front of them. By understanding of culture as a dynamic network of interactions, built by each individual along the relationships experienced in their lives and the displacement provided by tourism and communication, such as the network of relationships established from the common interest by travel, although each present character express different perspectives on the subject. From this, we question the understanding of a touristic experience from their physical structures and fixed, considering the main characters cognizant of this whole process, people with their own meaningful guidelines and space-temporal relations given the different realities that experience as its own baggage of life.
Fruto da constante movimentação de um turismólogo tentando se ambientar ao olhar antropológico, e suas nuances etnográficas, este trabalho busca complexificar a compreensão e utilização da(s) Experiência(s) Turística(s), tanto pela academia científica, como pelo “trade” turístico. Enquanto busca subsídios teóricos para compreensão proposta pela Antropologia da Experiência, de Victor Turner e Edward Bruner, e sua abordagem científica de uma Experiência, que destaca sua forma processual e ritual, pessoal e subjetiva, este trabalho tenta compreender porque uma história de vida só pode ser percebida e sentida pela pessoa que experiencia as realidades que defronta, nos diferentes espaços em que circula, ao longo de sua vida, e expressada da forma que desejar e conseguir representar. Imerso no ciberespaço, ao mesmo tempo em que experimenta metodologias para emersão de pistas nesse universo aberto, não fixo e plural, que possibilita expressões descentralizadas e desterritorializadas, de acordo com os interesses e diretrizes significativas de cada pessoa que as externa, busca narrativas em blogs de viagens que possam expressar as representações das pessoas a respeito de suas experiências turísticas, envoltas (frente) a um fenômeno que desloca indivíduos de seu cotidiano espaço e tempo, como o turismo, que, ao mesmo tempo, possibilita momentos de estranhamento, de confrontamento dramático entre seus conhecimentos prévios e a realidade a sua frente. Parte-se da compreensão de cultura como uma rede dinâmica de interações, construída por cada indivíduo ao longo das relações vividas na sua existência e pelos deslocamentos proporcionados pelo turismo e pela comunicação, como no caso da rede de relacionamentos estabelecida a partir do interesse comum pelas viagens, apesar de cada personagem presente expressar diferentes perspectivas sobre o assunto. A partir disso, questiona-se a compreensão de uma experiência turística a partir de suas estruturas físicas e fixas, sendo os personagens principais e cognoscentes de todo esse processo, pessoas com suas próprias diretrizes significativas e relações espaço-temporais diante das diferentes realidades que experienciar, conforme suas próprias bagagens de vida.
Keywords: Turismo; Antropologia; Ciberespaço; Tourist trade; Anthropology; Cyberspace